PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA CV. OPEN ARTO MADURAN LAMONGAN - Nawari, Nawari; Shoimah, Siti (Patria Artha University, 2021)
This study generally aims to determine the extent of the marketing mix relationship to purchasing decisions in CV. Open Arto Maduran Lamongan and to find out price variables, distribution channels, products and promotions that have a dominant influence and relationship to purchasing decisions products in CV. Open Arto Maduran Lamongan.The type of research used is a type of correlational research. Correlational research is a research that highlights the relationship between the variables studied and tests the hypotheses previously formulated. As for the purpose of the correlational research is to detect variations in variation in a variable relating to variations in variation on one or more other variables based on the correlation coefficient.The population in this study were consumers or customers in CV. Open Arto Maduran Lamongan. A population of 102 respondents, while the sample was set at 50% of the total population which was equal to 51 respondents. The sampling technique used in this study uses a simple random sampling technique, which is a simple random sampling technique, where the sample size is taken so that each research unit of the population is likely to be selected as a sample.From the results of the partial correlation test, it can be seen that the price variable (X1), distribution channel (X2), product (X3) and promotion (X4) have a partial effect on purchasing decisions (Y) on CV. Open Arto Maduran Lamongan. This can be proven from the results of the T-Variable Price (X1) count (2,584), Distribution Channels (X2) of (2,577), Product (X3) of (1,961) and Promotion (X4) of (5,943). With t table of (1.675). Then the T-count of the four variables is greater than t-table.